A noninvasive test for estimating myosin heavy chain of the vastus lateralis in females with mechanomyography. (January 2023) - Sontag, Stephanie A.; Sterczala, Adam J.; Miller, Jonathan D.; Deckert, Jake A.; Olmos, Alex A.; Parra, Mandy E.; Dimmick, Hannah L.; Gallagher, Philip M.; Fry, Andrew C.; Herda, Trent J.; Trevino, Michael A.
Highlights: First study to estimate myosin heavy chain in females via mechanomyography (MMG). A combination of MMG variables estimated myosin heavy chain (MHC) with 81% accuracy. MMG may noninvasively assess MHC of the vastus lateralis in females. Abstract: This study examined relationships between percent myosin heavy chain (%MHC) expression and mechanomyographic amplitude (MMGRMS ). Fifteen females (age ± SD=21.3 ± 5.3 yrs) completed isometric trapezoidal contractions at 30% and 70% maximal voluntary contraction (MVC). MMG was recorded from the vastus lateralis (VL). Participants gave a muscle biopsy of the VL post-testing. MMGRMS -torque relationships during the linearly varying segments were log-transformed and linear regressions were applied to calculate b terms (slopes). For the steady torque segment, MMGRMS was averaged. Correlations were performed for type I%MHC with the MMG variables. Multiple regression was utilized to examine prediction equations for type I%MHC. Type I%MHC was significantly correlated with the b terms during the increasing segment of the 70% MVC ( p = 0.003; r = -0.718), and MMGRMS during steady torque at 30% ( p = 0.008; r = -0.652) and 70% MVC ( p = 0.040; r = -0.535). Type I%MHC reduced the linearity of the MMGRMS -torque relationship during the high-intensity linearly increasing segment, and MMGRMS at a low- and high-intensity steady torque. A combination of MMG variables estimated type I%MHC expression with 81.2% accuracy. MMG recorded during a low- and high-intensity isometric trapezoidal contraction may offer a simple, noninvasive test for estimating type I%MHC expression of the VL in sedentary females.